In Times of Trouble: A Framework for Understanding Consumers’ Responses to Threats - Campbell, Margaret C; Inman, J Jeffrey; Kirmani, Amna; Price, Linda L (Journal of Consumer Research, 2020)
AbstractThe COVID-19 pandemic and the accompanying economic downturn have dramatically impacted the lives of consumers around the world. From a conceptual perspective, such health and economic threats can severely disrupt consumers’ sense of ontological security and elicit adaptive responses by both consumers and marketers. Given the opportune timing, this issue of the Journal of Consumer Research is focused on articles that address questions of consumers’ responses to external threats. The purpose of this introduction is to provide an organizing “conceptual tapestry” to connect the articles appearing in the issue. This framework is provided as a tool to help researchers structure their particular projects within the broader landscape of consumer threat response and to present some potential directions for future research. In conjunction with these articles, we hope that this conceptual framework will provide a point of departure for researchers seeking to enhance the understanding of how consumers and markets collectively respond over the short term and long term to threats that disrupt consumers’ routines, lives, or even the fabric of society.